(untitled) (The Research of Medical Science Review, 2024)
Background: Pancytopenia is a blood disorder in which blood cells become abnormal. So identification of the proper reason will aid in therapy. Objective: The objective of this study was to determine the etiological profile of pancytopenia in children at women and children hospital Karak city Material and method: The current cross-sectional study was carried out at women and children hospital Karak city over a period of 6 months from August 2023 to January 2024 after taking approval from the ethical board of the institute. Sample was collected through consecutive sampling technique and sample size was determined using WHO calculator. The sample size was 108 in our study. Bone marrow biopsy was performed in selected cases in accordance with provisional diagnosis. All the collected data was analyzed using SPSS version 23. Variables such as age, hemoglobin, TLC, and platelets were characterized as mean ± standard deviation. Categorical variables, such as gender and age, were presented in frequency and percentages. Results: A total of 108 individuals of both gender and different age groups (3 months -15 years) were enrolled in this study, out of which male were 68(62.9%) and females were 38(35.1%). 08.174 +3.3701 years was the mean age. The most prevalent age group in the study participants was 1- 5 years 37(34.2%), followed by age group 6 to 10 years 36(33.3%),11-15 age group 27(25%) and 1- 12 months 8(7.4%) respectively. Pancytopenia was most commonly caused by acute lymphoblastic leukemia, accounting for 53 (49%) cases. Aplastic anemia was seen in 22 instances (20%), followed by hypoplasia in 13 (12%). Conclusion: The current concluded that the most common cause of pancytopenia was acute lymphoblastic leukemia followed by aplastic anemia and bone marrow hypoplasia.